Correlation Between Sunshine Hours And Climatic Parameters At Four Locations In Uganda - Karum, K.; Banda, EJKB.; Mubiru, J.; Majaliwa, M. (Tanzania Journal of Science, 2007)
One of the most important factors in solar energy production is related to the predictability of sunshine hours. The objective of this study is to assess the correlation between sunshine hours and relative humidity, cloud cover, maximum and minimum temperature, for the purpose of identifying the most appropriate parameter(s) for the prediction of sunshine hours in Uganda. Climatic data for the meteorological stations of Entebbe, Mbarara, Tororo and Makerere, extending over a period of 15 years (1990-2005) was collected from the Department of Meteorology, Kampala. The data set included maximum temperature, minimum temperature, relative humidity at 6 am and at 12 noon, Cloud cover at 6 am and at 12 noon and Sunshine hours. A multiple regression technique was used to assess the correlation between sunshine hours and maximum and minimum temperatures, cloud cover at 6 am and at 12 noon and relative humidity at 6 am and at 12 noon. Results have shown that the availability of sunshine hours can be predicted by the use of maximum and minimum temperatures, relative humidity at 6 am and 12 noon and cloud cover at 6 am and at 12 noon in Uganda, but, principal components and factoraAnalysis have indicated that two parameters, especially relative humidity at noon or 6 am and Maximum temperature are enough to capture the variability of sunshine hours in Uganda.